Experiences of physiotherapy students in a clinical setting for elderly adults - S. L. Amosun (AOSIS, 2001)
The purpose of this study was to assess and describe qualitatively the learning experiences of physiotherapy students within the context of a clinical education setting where students learnt to provide care for elderly adults. Data collected over two years from students' diaries kept during the block, and individual or group interviews, were analysed. Two major themes were vital to the students, namely coping with disability and reduced functional ability in elderly adults, as well as dealing with death and dying. The study concluded that there is a need for clinical integration of the concepts of chronic disability, death and bereavement in physiotherapy education.